EVALUASI DIKLAT MODEL KIRKPATRICK PELATIHAN PEMBENTUKAN PENGENDALI EKOSISTEM HUTAN KEMENTERIAN LINGKUNGAN HIDUP DAN KEHUTANAN - Gamin Gamin (Jurnal Kewidyaiswaraan, 2021)
The education and training for the establishment of Forest Ecosystem Controllers that has been carried out in 2019 is not yet known for its efficiency, effectiveness, and impact on alumni performance in the field. This paper aims to describe the effectiveness of the training implementation and the impact of the training on the alumni's performance. Quantitative approach involving a population of 34 alumni is used for this study. Kirkpatrick's evaluation model was applied to determine the reaction, outcome, behavior, and impact of the training. Performance is assessed using a 360-degree method involving alumni, immediate supervisors, and alumni colleagues. The reaction to the training was rated "very good" by the trainees from various aspects of the assessment except for the laundry facilities and the front desk. The lessons learned by the participants during the training were very successful with the "satisfactory" graduation criteria achieved by 31 out of 34 participants. In general, training can significantly change behavior at work expressed by alumni, direct supervisors and co-workers. Training is explicitly stated to be able to provide results or have a real impact on the performance of individuals and organizations in the workplace. Meanwhile, alumni still feel less confident in carrying out professional development activities. The note from this research is that front desk services for training participants can be combined with the duties of security personnel at the security post. It is necessary to make separate details of work assignments in the field of Climate Change Control to be clearer. It is necessary to re-examine the provision of technical field subjects to be distinguished according to the field of work. It is necessary to increase the activities of scientific meetings to encourage alumni to carry out professional development activities.